2019
DOI: 10.1055/s-0039-1677709
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Minocycline on Fat Graft Survival and Apoptotic Pathway

Abstract: Variable absorption rate is one of the biggest problems of fat grafting and one of the most important causes of fat graft volume loss is apoptosis. Minocycline is a tetracycline derivative and besides its antibacterial capacity, it has been widely using for anti-apoptotic effects. This study was designed to investigate the effect of minocycline on fat graft survival and adipocyte apoptosis. A total of two main and eight subgroups were designed and a total of 48 experimental animals, 6 in each group, were used.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…That is why there is no alteration in the epidermal thickness. This is also being the findings of Guneyet al that demonstrate the antiapoptotic effects of minocycline on fat graft and observed statisticallysignificant apoptosis inhibition 21 . This has also being proven in the study conducted by Abbaszuddenet al who found that minocycline protects neurons from caspase activation through decrease release of cytochrome C from mitochondria and also reduces the levels of TNF 22 .…”
Section: Groupsupporting
confidence: 70%
“…That is why there is no alteration in the epidermal thickness. This is also being the findings of Guneyet al that demonstrate the antiapoptotic effects of minocycline on fat graft and observed statisticallysignificant apoptosis inhibition 21 . This has also being proven in the study conducted by Abbaszuddenet al who found that minocycline protects neurons from caspase activation through decrease release of cytochrome C from mitochondria and also reduces the levels of TNF 22 .…”
Section: Groupsupporting
confidence: 70%
“…Rapid vascularisation seems crucial, 30 and until then the graft has to be protected from harmful impacts such as mechanical cues or infectious agents. Moreover, antiapoptotic effects on free fat grafts exerted by certain antibiotic substances have been postulated 31 . Hence, most surgeons prefer to add antibiotics to their postoperative regime following autologous lipotransfer with the goal of maximising safety of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Adipocytes represent the major cell type in absorbed cell type in the fat graft. In the model of the fat implant to the dorsal area of rats, Güney et al verified that the adipocyte apoptosis could be inhibited by utilizing minocycline, thereby increased fat graft survival characterized by bigger graft volume, better fat structures coupled with more vascular 16 . And this apoptosis could be antagonized by synthetic glucocorticoid and insulin-like growth factor-1 (IGF-1) 17 .…”
Section: Adipocyte Apoptosismentioning
confidence: 99%